2015
DOI: 10.1097/bcr.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Adrenal Insufficiency in Critically Ill Burned Patients

Abstract: Adrenal insufficiency (AI), whether etomidate-induced or secondary to critical illness-related corticosteroid insufficiency (CIRCI), is a common and under appreciated problem in the intensive care unit intensive care unit (ICU). However, AI is often difficult to identify and diagnose in the critically ill. The pathophysiology and ideal management of etomidate-induced AI and CIRCI, especially in burn patients, is unknown. Many studies, however, have examined the prevalence of and risk factors for developing AI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In 1983, Ledingham and 2 other research groups [ 1 ] found that ETO had the effect of inhibiting the synthesis and release of human adrenocortical hormones. Other researchers [ 2 6 ] found that the peak effect of ETO in inhibiting the adrenocortical function was 6–8 h after a single-dose injection of ETO, and restored to normal limits spontaneously within 24 h. Continuous injection of ETO could prolong this inhibitory effect beyond 24 h.…”
Section: Introductionmentioning
confidence: 95%
“…In 1983, Ledingham and 2 other research groups [ 1 ] found that ETO had the effect of inhibiting the synthesis and release of human adrenocortical hormones. Other researchers [ 2 6 ] found that the peak effect of ETO in inhibiting the adrenocortical function was 6–8 h after a single-dose injection of ETO, and restored to normal limits spontaneously within 24 h. Continuous injection of ETO could prolong this inhibitory effect beyond 24 h.…”
Section: Introductionmentioning
confidence: 95%
“…Adrenal insufficiency, whether caused by etomidate or secondary to corticosteroid insufficiency associated with critical illness, is a common problem in the intensive care unit. 8 Studies have demonstrated that nearly 50% of critically ill patients (e.g., those with traumatic brain injury) have adrenal insufficiency, which is associated with age, the severity of the injury, and the administration of etomidate. High doses of cortisol should not be prescribed in severe sepsis.…”
mentioning
confidence: 99%